Actors' dynamics toward performance-based budgeting: a mix of change and stability?. Issue 2 (3rd June 2019) - Mauro, Sara Giovanna; Cinquini, Lino; Sinervo, Lotta-Maria
Abstract : Purpose: The purpose of this paper is to analyze the under-investigated role played by different key organizational actors engaged in the practice of performance-based budgeting (PBB) (e.g. Ministry of Finance, National Audit Office, Sectoral Agencies) to explore how they influence the practice of PBB, contributing to lead the change or create resistance toward it. Design/methodology/approach: The empirical evidence has been collected through a multiple case study based on semi-structured interviews and document analysis in Sweden and Finland, which have long traditions with PBB, and has been interpreted through the lens of institutional and organizational change theory. Findings: The results show that, despite the lengthy experiences with PBB, the lack of sound dynamics across key actors makes the budgetary use of performance information limited and partial, placing the reform in a "gray area" between the complete implementation of the practice and the total resistance toward it. Originality/value: The knowledge obtained from the exploratory analysis has relevant implications for understanding differences and similarities across key organizational actors and underlining their crucial role in making a change feasible. Indeed, PBB may represent a radical change even in presence of embedded performance management systems.